Efficacy of Chinese Medicine on Postoperative Rehabilitation of Non-small Cell Lung Cancer (NSCLC), a Randomized Controlled Study - Yifeng Gu MD; Yichao Wang MD; Huiling Zhou MD; Ao Qi PhD; Guanjin Wu MM; Jiaqi Li MMed; Congmeng Zhang MMed; Yong Yang MD; Jialin Yao MD; Wenxiao Yang PhD; Lingzi Su MMed; Yi Liu MMed; et al. (Integrative Cancer Therapies)
Background: With an increasing number of non-small cell lung cancer (NSCLC) patients being offered surgical treatment, postoperative rehabilitation is also being increasingly emphasized. Traditional Chinese medicine (TCM) holds promise for enhancing postoperative recovery, with treatment methods still in refinement. This study aims to evaluate the efficacy of Chinese herbal decoction and Liuzijue exercises in NSCLC patients during the rapid postoperative recovery period. Methods: A randomized, parallel-group clinical trial assigned 50 patients to receive Chinese herbal medicine and Liuzijue exercise plus symptomatic treatment, and 49 to symptomatic treatment alone. Treatment continued until postoperative complications resolved, chest tubes were removed, and no abnormal examination findings were reported. The primary outcome was Quality of Life Questionnare-Core 30 (QLQ-C30) score. Secondary outcomes included MOS item short form 36-Item Short Form Health Survey (SF-36) score, rate of complications, six-minute walk test (6MWT) distance, Leicester Cough Questionnaire (LCQ) score, numerical rating scale (NRS) score, and functional activity score (FAS). Results: Significant improvements in role (MD: 12.15, 95%CI: 2.99-21.32, P  < .05) and social functioning (MD: 10.25, 95%CI: 1.72-18.78, P  < .05) were observed in the intervention group vs. controls, as measured by QLQ-C30. The intervention group showed better post-treatment SF-36 scores in Role-Physical (RP), Social Function (SF), Role-Emotional (RE), and Mental Health Summary (MCS) ( P  < .05). The complication rate was lower in the intervention (20.00%) than the control group (44.44%) ( P  < .05). The intervention group also had a significant increase in FAS scores ( P  < .05) and covered a better 6MWT distance ( P  < .05). Conclusion: Chinese herbal decoction and Liuzijue exercises during the rapid recovery period after lung cancer surgery enhanced patients’ QoL and physical endurance, and mitigated complications. Trial registration: This tial was registered with chictr.org.cn (Registration number:ChiCTR2100044776).